Persons with (dis)Abilities - Baldridge,David; Beatty,Joy; Böhm,Stephan; Kulkarni,Mukta; Moore,Mark (2015)
This chapter examines workplace discrimination faced by persons with (dis)abilities. It begins by discussing usage, meaning, and effects of the word “disability” and the related term “persons with disabilities.” It then considers the diversity of conditions and experiences among persons with (dis)abilities by reviewing extant research on people with five common disabling conditions (i.e., mobility, seeing, hearing, chronic illness, and psychiatric conditions). It also examines the importance of national context by taking a closer look at research on the experiences of people with (dis)abilities in five nations (i.e., United States, Canada, Germany, India, and China). By separately highlighting extant research on a few common conditions and nations, the chapter’s intent is to show the need for more research on specific conditions in specific work and national contexts, as well as the need for research integrating and summarizing these focused studies.
Keywords: Management